Arranging and ordering in autism spectrum disorder: Characteristics, severity, and environmental correlates. (September 2013) - Rodriguez, Nicole M.; Thompson, Rachel H.; Stocco, Corey S.; Schlichenmeyer, Kevin
Abstract: Background There is a need for a more accurate characterisation of higher level restricted and repetitive behaviour (RRB) in autism spectrum disorder (ASD), including why it might be considered problematic and events associated with its occurrence. Method We selected one form of higher level RRB—arranging and ordering—that was rated as severe for a large percentage of the population sampled. We interviewed 20 students' teachers and conducted naturalistic observations for 15 of those students. Results The characteristics of arranging and ordering varied across, and sometimes within, individuals. Problems associated with compulsive-like 1 behaviour also varied, with several unanticipated reported problems. With the exception of attention, social consequences were relatively infrequent. Conclusions These data highlight the need for research on the assessment and treatment of arranging and ordering and clinical attention to compulsive-like behaviour in ASD. Interviews and naturalistic observations are useful for structuring additional observations and analyses.